A TEOLOGIA DO COMPROMISSO NO PENSAMENTO DE ELLEN G. WHITE: UMA PERSPECTIVA DA LIBERDADE CRISTÃ - Teixeira, Carlos Flávio (2012)
This dissertation presents a non-exhaustive approach about the theme of freedom from the perspective of a North American Protestant Christian theologian named Ellen G. White. The dissertation starts with a study about her life and the social-cultural and geopolitical contexts, in which she lived in, approaching her literary writings and the importance of her way to systematize her thoughts in order to understand her reasoning about the proposed theme. It is taken as a criterion for analysis her system of organizing her thoughts in three theological lines of thinking named respectively Integral Theology, Theology of Commitment, and the Theology of Discipleship that together constitute her theological perspective of freedom. The first line of reasoning justifies the reasons of freedom, the second one explains how liberty occurs in human being, and the third one explains the itinerary of its positive exteriorization for humanity. The dissertation continues exploring the concepts, foundations, features and thematic developments of each element which comprises the theological itinerary that has been mentioned, and highlighting the theologians that strongly influenced the author and pointing out her closest perspectives compare to the posteriors theologians. The dissertation concludes proposing that, by the authors perspective, freedom is a significant expression of a committed life to serve with love in a piety way. Thus, freedom is a condition lived for those who believe and surrender themselves to God, experiencing an enduring life of love and self-sacrificing service to the neighbor, a reality that is witnessed through a genuine Christian piety. And lastly, the dissertation challenges the reader to an urgent perception, critical thinking, and a balanced proactive reaction towards the humanists ideologies of an exclusive anthropocentric matrix, presenting them as the main foundations of postmodern misconceptions about freedom. Given this reality, the dissertation proposes to rehumanize the idea of liberty through a theocentric perspective, by returning to God and His word, and for this action Ellen G. White s proposal seems to be a Teo-humanizing potential of great value that may enable even the harmonious development of human wholeness.